Reconfigurable THz Fixed-Frequency Beamscanning Through a Liquid-Crystal-Loaded Leaky Waveguide Operating in Its Fundamental TE Mode - Walter Fuscaldo; Elahehsadat Torabi; Dimitrios C. Zografopoulos; Danilo Erricolo; Romeo Beccherelli (IEEE Access, 2023)
A rectangular metallic leaky waveguide loaded with liquid crystals (LC) and operating in its fundamental TE mode at 1 THz is proposed to mitigate the well-known trade-off between directivity and tunable angular range of dynamic beamscanning antennas. The radiating aperture consists of a partially reflecting sheet (PRS) realized through a one-dimensional array of longitudinal slots etched on one of the metallic walls of the waveguide to efficiently couple with the propagating TE leaky mode. The antenna performance is evaluated by defining suitable figures of merit that take into account the beamscanning feature and the gain peak. These figures of merit are evaluated for different combinations of the antenna design parameters. After optimization, a tunable angular range of about 28° is reached, while maintaining a gain of around 7 dBi. A leaky-wave analysis of a simplified model of the structure allows to design the antenna without resorting to computationally expensive optimization processes. More rigorous models are then considered to accurately analyze the LC dynamics and the radiating properties of the PRS. The three-dimensional structure is finally validated through full-wave simulations, showing a remarkable agreement with the theoretical predictions obtained with the simplified model.